EFECT OF LEAF FERTILIZER ON SECOND TREATMENT TO THREE GENOTYPES CORN EFFICIENT CROPS IN TIDAL LAND - Andesta, Andesta; Munandar, Munandar; Yakup, Yakup (BIOVALENTIA: Biological Research Journal, 2019)
This study aims to determine the effect of leaf fertilizer on three nutrient efficient corn genotypes in tidal land. This research was coductedÂ  in Village Mulia sari, Sub-district Tanjung Lago, District Banyuasin, South Sumatra in the noble village of Sari Tanjung Lago sub-district from August to December 2017. This study uses the Split Plot Design consisting of 3 factors, namely the first factor of genotype, the second factor is the dose of urea A0 = 0 kg, A1 = 250 kg, A2 = 300 kg and the third factor of leaf fertilizer consists of: P0 = (control without spraying), P1 = 30 days of spray, P2 = 45 days of spray, P3 = 30 + 45 days of spray, P4 = 60 days of spray, P5 = 75 days of spray, P6 = 60 + 75 days of spray. repeated three times. Observation results used of 300 kg of urea fertilizer and leaf fertilizer had a good influence on the growth of G3 corn genotypes and the production of corn plants in tidal land. The combination of giving 300 kg of urea fertilizer + leaf fertilizer gives a pretty good influence on the growth of G3 corn genotypes with a production of 7.44 Ton/hectares